IS IT STILL WORTH TREATING PATIENTS WITH PERIODONTAL DISEASE IN THE NEW ERA OF DENTISTRY? - Canabarro, Antonio (Revista Científica do CRO-RJ (Rio de Janeiro Dental Journal), 2021)
Current advances in the medical field have facilitated the diagnosis and treatment of various diseases. 1 As periodontal disease (PD) is a widespread chronic inflammatory illness, reaching up to 80% of the Latin America population, 2 the scientific and technological arsenal for its management are made available to dental professionals during academic learning or through continued education. However, despite all knowledge related to PD, it is especially intriguing that even though several studies have shown the possibility of controlling PD for long periods of time, through a regular and effective mechanical control of the biofilm,3 it remains so prevalent.